2021
DOI: 10.35371/aoem.2021.33.e19
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of measles, mumps, rubella, and varicella-zoster antibodies in new female nurses in the Republic of Korea

Abstract: Background For health care workers, immune management plays an important role in the protection against infectious diseases. This study investigated the seroprevalence of measles, mumps, rubella, and varicella-zoster in newly employed female nurses. Methods We conducted a survey on the seroprevalence of measles, mumps, rubella, and varicella-zoster in newly employed female nurses at a university hospital from 2011 to 2019, before the nurses were given their department p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The present study showed 91% seropositivity for VZV among the HCWs. Our finding was similar to previous studies that reported a seroprevalence of over 90% in Korean adults [15,21,22,33]. The seroprevalence of VZV was higher than 90% in other countries, including Finland, Denmark, Japan, and Singapore [34][35][36][37].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study showed 91% seropositivity for VZV among the HCWs. Our finding was similar to previous studies that reported a seroprevalence of over 90% in Korean adults [15,21,22,33]. The seroprevalence of VZV was higher than 90% in other countries, including Finland, Denmark, Japan, and Singapore [34][35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…These results could meet the population immunity threshold for varicella [38]. However, seroprevalence significantly decreased in younger HCWs in the present study, and this trend was also observed in another study conducted in Korea [15]. Furthermore, the seroprevalence of VZV in the younger population was lowered in Singapore [34].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the occupational setting a screening and vaccination strategy for healthcare workers is needed, especially considering that there is usually a low correlation between self-reported immunity and seropositivity [ 21 ]. Some Authors suggest to provide measles-mumps-rubella vaccination without performing serologic testing for new HCWs, and the varicella-zoster vaccination only for those who are negative after serologic testing, using the compulsory worker health examinations as a possible setting [ 22 ].…”
Section: Discussionmentioning
confidence: 99%